2016
DOI: 10.18267/j.pep.553
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Sustainability in Central and Eastern European Countries - A Post-Crisis Assessment

Abstract: The aim of this paper is to investigate public fi nance sustainability for a selected group of ten Central and Eastern European countries. In order to assess the fi scal sustainability of these countries we extend standard analyses typically used for developed countries to our group of ten CEE countries. To assess fi scal sustainability we use panel stationarity and cointegration tests, as well as estimates of certain parameters of fi scal reaction functions. Our research shows that despite the fi nancial turm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
2
21
1
Order By: Relevance
“…On the whole, our results are in line with majority of empirical studies for the CEE countries which report problems with fiscal sustainability, for example Aristovnik and Bercic (2007), Krejdl (2006), Mihaljek (2009), or rather weak evidence in favour of sustainable fiscal indicators (Krajewski, Mackiewicz, & Szymańska, 2016;Tronzano, 2017). In order to correct fiscal imbalances, it is necessary to close loopholes in the tax system in the first place or implement necessary expenditure cuts, for example on natural gas subsidies for households.…”
Section: Econometric Methodology and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…On the whole, our results are in line with majority of empirical studies for the CEE countries which report problems with fiscal sustainability, for example Aristovnik and Bercic (2007), Krejdl (2006), Mihaljek (2009), or rather weak evidence in favour of sustainable fiscal indicators (Krajewski, Mackiewicz, & Szymańska, 2016;Tronzano, 2017). In order to correct fiscal imbalances, it is necessary to close loopholes in the tax system in the first place or implement necessary expenditure cuts, for example on natural gas subsidies for households.…”
Section: Econometric Methodology and Resultssupporting
confidence: 90%
“…More recently, it is found that fiscal policy in Poland is 'weakly sustainable', as there is bi-directional causality between expenditure and revenues (Tronzano, 2017). On the whole, it is suggested that sustainability of public debt stock in the CEE countries has improved (Wysocki, 2017), but only 'in a weak sense' (Krajewski, Mackiewicz, & Szymańska, 2016). However, it is established that that current public debt ratio as of 2015 for Bulgaria and Romania is not sustainable (Bökemeier & Stoian, 2016).…”
Section: Fiscal Sustainability: Theory and Empirical Studiesmentioning
confidence: 99%
“…After tests of integration order and cointegration analysis, we estimated the fiscal reaction function. The structure of the fiscal reaction function is in line with the former specifications by Bohn [2007] and Krajewski et al [2016]. Because we used quarterly data, all variables were lagged by four instead of one: Next, we estimated the fiscal reaction function for Poland in our sample of 2004 Q1-2017 Q2 ( Table 4).…”
Section: Results Of the Econometric Analysismentioning
confidence: 80%
“…Several recent studies have used these different approaches to analyze the fiscal sustainability for a set of the new EU member states, including Poland. For example, Krajewski et al [2016] have used panel stationarity and cointegration tests, as well as estimates of certain parameters of the fiscal reaction function, for Bulgaria, the Czech Republic, Estonia, Lithuania, Latvia, Poland, Slovakia, Romania, and Hungary. They find that despite financial turmoil, these countries demonstrated the existence of a longterm relationship between revenues and expenditures and they have statistically relevant parameters of the fiscal reaction function.…”
Section: Measuring Fiscal Sustainability: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation